An Academic’s Role? Supporting Student Wellbeing in Pre-university Enabling Programs - Crawford, Nicole; Johns, Susan (Journal of University Teaching and Learning Practice, 2018)
Student wellbeing and mental health are increasingly a concern of universities. Most universities provide central counselling services and, in recent years, some have introduced wellbeing programs. However, an unrecognised source of support and pastoral care for students is academic staff. This pilot research project explored the experiences of academic staff in one university’s enabling programs in terms of the type of support academic staff provide (academic and/or non-academic), how equipped they perceive they are to support their students, and how this role impacts on them. The study is qualitative; interviews were conducted and a thematic analysis undertaken. It was found that academic staff viewed supporting their students as part of their role, particularly due to the diverse and complex nature of the cohort, and noted that students sought support from them for academic and non-academic issues because they had a rapport with them, trust and regular contact. A positive finding was that the academic staff had clear boundaries and lines of referral, which means they were not taking on pseudo-counselling roles. How equipped staff perceived they were and how the support role impacted on them varied depending on their teaching role. The findings in this exploratory study prompt a re-conceptualisation of the academic role. The article proposes a model of support that is holistic, student and course centred, and that integrates the centrally-located university counsellors. Furthermore, it posits that at the core of the enabling programs is a philosophy of care.